Meta-Analysis of Knee Joint Function Recovery after Anterior Cruciate Ligament Reconstruction by Accelerated Rehabilitation Surgery. (29th June 2022) - Xu, Junxiang; Zheng, Minzhe; Feng, Zongxian; Pan, Lingxiao; Peng, Zhaoxiang
Abstract : Objective . This investigation was undertaken to systematically assess the impact of increasingly rapid recovery treatment on the functional status of the knee following anterior cruciate ligament restructuring. Methods . Computer search from the establishment of the database to March 2022 in China Knowledge Network Database (CNKI), PubMed, EMBASE, ScienceDirect, CochraneLibrary, China VIP Database, Wanfang Database, and China Biomedical Literature Database (CBM). The control group was given only traditional rehabilitation training, and the observation group was treated with perioperative accelerated rehabilitation surgery intervention randomized controlled trial (RCT). Data for all included studies were extracted by two independent researchers, and the risk of bias for the quality of each included study was assessed by the Cochrane Handbook 5.1.0 criteria. Meta-analysis of the collected data by using RevMan5.4 statistical software. Results . A total of 593 articles were retrieved from the computer database and 8 RCT articles with a total of 636 samples were finally included for meta-analysis. According to the Jadad scale, the RCT score of 8 articles was ≥4 points. Meta-analysis was performed on the postoperative VAS scores of the ERAS group and the traditional rehabilitation group, and the heterogeneity test showed Chi 2 = 288.60, d f = 5, P < 0.00001, and I 2 = 99%. There was a statistically significant difference in the postoperative VAS scale between the intervention and the traditional rehabilitation model P < 0.05 . Eight articles reported the effect of accelerated rehabilitation surgery on the recovery of knee joint motion after ACL rehabilitation. After meta-analysis, the heterogeneity test showed Chi 2 = 314.98, d f = 7, P < 0.00001, and I 2 = 98%, and it can be concluded from the analysis that, compared with the traditional rehabilitation model, the enhanced rehabilitation surgery has an effect on the joint function after anterior cruciate ligament reconstruction. The improvement effect was more significant, and the difference was statistically significant P < 0.05 . Four articles reported the effect of enhanced recovery after surgery intervention on the range of motion of the knee joint of patients, the heterogeneity test showed Chi 2 = 117.52, d f = 2, P < 0.00001, and I 2 = 98%, through analysis, and compared with the traditional rehabilitation model and the enhanced recovery. The effect of surgery on the range of motion of the knee joint after ACL reconstruction was more significant, and the difference was statistically significant P < 0.05 . The effect of enhanced recovery after surgery and traditional rehabilitation mode on the incidence of postoperative adverse reactions in patients undergoing ACL reoperation was analyzed. The results of heterogeneity test showed that Chi 2 = 1.59, d f = 2, P = 0.66 > 0.05, and I 2 = 98%, and the analysis showed that, compared with the traditional rehabilitation mode, enhanced rehabilitation surgery can significantly reduce the risk of adverse reactions after anterior cruciate ligament reconstruction P < 0.05 . An inverted funnel plot was used to analyze publication bias in studies with quality of life as an outcome measure. The results showed that Egger's test P = 0.0005 < 0.001 suggesting that there may be a certain degree of publication bias. Conclusion . The existing research evidence shows that accelerating the reconstruction of anterior cruciate ligament can effectively promote the recovery of knee joint function, reduce the pain of patients, and reduce postoperative complications. However, more research is needed to further verify this.